Clinical Correlation of Prostatic Calculi With Semen Parameters in Adult Men With Fertility Intention. Issue 3 (18th May 2019) - Chen, Tong; Tian, Linlin; Bai, Gang; Ma, Gang; Tang, Rong; Liu, Jiaolong; Pang, Qingyang; Wang, Xianlong; Lu, Jiaju
To investigate the correlation of prostatic calculi (PC) with semen parameters in men with fertility intention, this retrospective case–control study enrolled 1, 303 participants ranging from 20 to 59 years old; 725 were diagnosed with PC using abdominal ultrasonography. Patients with PC were classified into the type A calculi group (discrete and small echoes) and type B calculi group (coarse and large masses of multiple echoes). Five hundred and seventy-eight men without PC were recruited for the control group. The clinical data of each group were collected and analyzed. The total motility was significantly lower for subjects with type B calculi (41.84% ± 17.50%) than for subjects in the type A calculi (51.78% ± 20.84%; p < .001) and control (54.47% ± 20.74%; p < .001) groups. The percentage of progressively motile was significantly lower for the type B calculi (31.66% ± 14.68%) group than the type A calculi (40.17% ± 17.09%; p < .001) and control (41.83% ± 17.05%; p < .001) groups. The results of the hypo-osmotic swelling test yielded significantly lower percentages in the type B calculi group (59.88% ± 17.13%) than the type A calculi (65.28 ± 14.43%; p = .005) and control (66.92 ± 16.12%; p < .001) groups. The type B calculi group had a significantly higher percentage of round cell concentration than control (4.5% vs. 1.0%; p = .007) did. Small and discrete PC may not influence semen quality among adult men with fertility intention, but larger and coarser PC are associated with decreased sperm motility.